1998
DOI: 10.1017/s0950268897008376
|View full text |Cite
|
Sign up to set email alerts
|

A community outbreak of Salmonella berta associated with a soft cheese product

Abstract: In September 1994, a complaint was registered at a public health unit concerning a cheese product. In addition, public health laboratories in Ontario reported an increase in the number of isolates of Salmonella berta from patients with diarrhoeal illness. A clinical, environmental and laboratory investigation was initiated to determine the nature of this outbreak. Isolates of Salmonella berta were compared using large fragment genomic fingerprinting by pulsed-field gel electrophoresis (PFGE). By late October, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 12 publications
(12 reference statements)
0
19
0
1
Order By: Relevance
“…Cross-contamination has been found to be the cause of a number of foodborne outbreaks with Salmonella. For several of the outbreaks the cause is believed to be lack of or insufficient cleaning and disinfection of equipment and surfaces (Ellis et al, 1998;Evans et al, 1996;Giraudon et al, 2009;Hennessy et al, 1996;Llewellyn, Evans, & Palmer, 1998;Podolak, Enache, Stone, Black, & Elliott, 2010;Reij & Aantrekker, 2004;Rowe et al, 1987). An example was an outbreak of salmonellosis in USA associated with the consumption of ice cream, where an ice cream premix was transported in insufficiently cleaned tanker trailers that had previously hauled nonpasteurised liquid eggs containing S. Enteritidis (Hennessy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-contamination has been found to be the cause of a number of foodborne outbreaks with Salmonella. For several of the outbreaks the cause is believed to be lack of or insufficient cleaning and disinfection of equipment and surfaces (Ellis et al, 1998;Evans et al, 1996;Giraudon et al, 2009;Hennessy et al, 1996;Llewellyn, Evans, & Palmer, 1998;Podolak, Enache, Stone, Black, & Elliott, 2010;Reij & Aantrekker, 2004;Rowe et al, 1987). An example was an outbreak of salmonellosis in USA associated with the consumption of ice cream, where an ice cream premix was transported in insufficiently cleaned tanker trailers that had previously hauled nonpasteurised liquid eggs containing S. Enteritidis (Hennessy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1995). In addition to IS200 typing and ribotyping, macrorestriction profiling by pulsed‐field gel electrophoresis (PFGE) analysis is now recognized to be one of the most reliable and discriminative tools for epidemiological typing of Salmonella isolates belonging to various serovars, including Typhimurium (Schwarz and Liebisch 1994; On and Baggesen 1997), Berta (Ellis et al . 1998), Brandenburg (Baquar et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are currently more than 2,500 identified serotypes of Salmonella, Salmonella enterica serovars Enteritidis and Typhimurium most commonly cause human disease. It is believed that some salmonellosis outbreaks were due to the inexistent or deficient cleaning and disinfection of surfaces and tools (e.g., Ellis et al 1998;Reij and Aantrekker 2004;Giraudon et al 2009;Podolak et al 2010). In fact, several studies have shown that these bacteria are able to colonize various food contact surfaces (e.g., Teixeira et al 2007a;Oliveira et al 2006;Rodrigues et al 2011), and it was also reported that Salmonella adhere and form biofilms in food processing facilities (Joseph et al 2001).…”
Section: Main Foodborne Pathogensmentioning
confidence: 99%